Addressing Challenges in Narrative Writing: An Error Analysis of Eleventh Grade Senior High School Students' Use of Simple Past Tense - Sri Ade Fitria; Mukhlash Abrar (EduInovasi: Journal of Basic Educational Studies, 2024)
The motivation behind this review is to distinguish errors in the utilization of the basic past tense by 11th grade at Madrasah Aliyah Nurul Jihad in Indragiri Hilir. The exploration technique is descriptive qualitative, with an emphasis on information got from the writing tests. The information showed that students made errors in utilizing the straightforward past tense, which were delegated omission, addition, misformation, and misordering. There were 104 errors found, including 43 omissions, 16 additions, 20 misformations, and 25 misorderings. The most prevalent type of error was omission (42%), followed by misordering (24%), misformation (19%), and addition (15%). The prevalence of omission errors suggests that students struggle with understanding and applying the simple past tense in their narrative writing, often resulting in incomplete sentences or omitted words. To improve, students should engage in more practice with narrative text writing to enhance their grasp of the simple past tense.